2011
DOI: 10.1590/s1415-47572011000400013
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide diversity and molecular evolution of the WAG-2 gene in common wheat (Triticum aestivum L) and its relatives

Abstract: In this work, we examined the genetic diversity and evolution of the WAG-2 gene based on new WAG-2 alleles isolated from wheat and its relatives. Only single nucleotide polymorphisms (SNP) and no insertions and deletions (indels) were found in exon sequences of WAG-2 from different species. More SNPs and indels occurred in introns than in exons. For exons, exons+introns and introns, the nucleotide polymorphism π decreased from diploid and tetraploid genotypes to hexaploid genotypes. This finding indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…AG-like group C-class genes from monocots contain two clades, WAG-1 and WAG-2 clade, WAG-1 (WAG-1-1AS, WAG-1-1BS, WAG-1-1DS) formed the WAG-1 clade together with wheat TaAG-1, barely HvAG2, maize ZAG1, and rice OsMADS58, whereas WAG-2 grouped into the WAG-2 clade with wheat AGL39, WM29A, and WM29B, and barley HvAG1, maize ZMM2 and rice OsMADS3 (Figure 4). Using the deduced amino acid sequences, phylogenetic analyses showed that WAG-1 and WAG-2 are orthologs of the rice AG-type genes, Os-MADS58 and OsMADS3, respectively (Hirabayashi and Murai, 2009;Wei et al, 2011). WAG-1 and WAG-2 have also been referred to as TaAG-2 and TaAGL39, respectively (Zhao et al, 2006;Paolacci et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…AG-like group C-class genes from monocots contain two clades, WAG-1 and WAG-2 clade, WAG-1 (WAG-1-1AS, WAG-1-1BS, WAG-1-1DS) formed the WAG-1 clade together with wheat TaAG-1, barely HvAG2, maize ZAG1, and rice OsMADS58, whereas WAG-2 grouped into the WAG-2 clade with wheat AGL39, WM29A, and WM29B, and barley HvAG1, maize ZMM2 and rice OsMADS3 (Figure 4). Using the deduced amino acid sequences, phylogenetic analyses showed that WAG-1 and WAG-2 are orthologs of the rice AG-type genes, Os-MADS58 and OsMADS3, respectively (Hirabayashi and Murai, 2009;Wei et al, 2011). WAG-1 and WAG-2 have also been referred to as TaAG-2 and TaAGL39, respectively (Zhao et al, 2006;Paolacci et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these point mutations were synonymous substitutions that did not alter the underlying amino acid sequences. SNPs are the most abundant type of DNA variation of plant genomes (Brookes 1999; Wei et al 2011). However, their frequency varies among the different plant species (Wei et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs are the most abundant type of DNA variation of plant genomes (Brookes 1999; Wei et al 2011). However, their frequency varies among the different plant species (Wei et al 2011). Inbred rice and Arabidopsis display one SNP in every 300 bp (Schmid et al 2003), while outbreeding maize has one SNP/60 bp (Ching et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seed shattering (or loss thereof) has been associated with an SNP through a GWAS aimed at unraveling the evolution of rice that led to its domestication [141]. SNPs have also been used to study the evolution of genes such as WAG-2 in wheat [142]. Algorithms such as neighbor-joining and maximum likelihood implemented in the PHYLIP [143] and MEGA [144] software are commonly used to generate phylogenetic trees.…”
Section: Applications Of Snpsmentioning
confidence: 99%